Security Communities, Defence Policy Integration and Peace Operations in the Southern Cone: An Argentine Perspective - Diamint, Rut (2011)
This article contends that the combined efforts of the Ministries of Foreign Affairs and Defence in nine countries of South and Central America, the ‘G9’, can be considered as a nascent but not yet developed security community. Due to a growing capacity for crisis management that includes the search for political solutions to structural conflict and to political, economic and social deficits in Haiti, the article demonstrates that South American countries are developing a novel concept for post-conflict response. Finally, in the context of democratization, Argentina's participation in peace missions generates domestic elements strongly committed to peace operations.